Industrial training report: netEON Touch Solution / Muhammad Hazim Azahari - Azahari, Muhammad Hazim (Perpustakaan Tengku Anis, 2017)
Based on the period.from 02 February 2017 to 30 June 2017 at Technician at netEON Touch Solution Sdn Bhd. The activity while during internship consists of supports on site and technician for the company. In period of time given, there are many work, activity and also task being given in order to enhance and improve daily task. As this company, mostly toward development of self-service kiosk.